Answer:
(3x - 4)(8x - 3)
Step-by-step explanation:
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 24 × 12 and sum = - 41
The required factors are - 32 and - 9
Use these factors to split the x- term
24x² - 32x - 9x + 12 ( factor the first/second and third/fourth terms )
= 8x(3x - 4) - 3(3x - 4) ← factor out (3x - 4) from each term
= (3x - 4)(8x - 3) ← in factored form
Answer:
(2x+1)(2x−1)
Step-by-step explanation:
Pythagorean Theorem A2+B2=C2
625=25+C2
600=C2
Square root of 2 each side
10 Square root of 6 Or 24.494897
Answer:
c = 53 miles
Step-by-step explanation:
a^2 + b^2 = c^2
45^2 + 28^2 = c^2
2,025 + 784 = c^2
2809 = c^2
c = 53